STAGNASI TAFSIR FALSAFI DAN KURIOSITAS AL-QURAN : (Analisis Pemikiran Muhammad Husain Al-Zahabi) - Kurdi Fadal (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2022)
Tafsir Falsafi (philosophical exegesis) is one of of the Islamic intellectual resource that have occupied the intellectualism of Muslim thinkers since the early period. However, the epistemological side of the interpretation model was problematic, as it creates controversy among the readers. Today, the controversy is still frequently found from some thinkers of the Quranic studies. This paper discusses Muhammad Husain al-Zahabi’s thoughts on philosophical interpretation. Utilized a library research, this paper uses content analysis method to analyze al-Zahabi's thoughts. This paper emphasizes that in al-Zahabi's works, especially in his book, al-Tafsir wa al-Mufassirun, he rejected philosophical interpretations which only make products of Greek philosophical thought as the main tools Quranic interpretation. Offered by Muslim philosophers such as al-Farabi, Ibn Sina and the Ikhwanus Shafa, It was considered by al-Zahabi to be very dangerous for the Muslims faith. In addition, their offer of interpretation model is considered far from the truth value of religion (Islam). However, this assessment actually confirms the stagnation of philosophical interpretation in the constellation of Islamic thought so that it has an impact on the weak implementation of the Qur'anic curiosity.